2020
DOI: 10.1111/jce.14788
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic approach to diagnosis and ablation of patients with permanent junctional reciprocating tachycardia associated with complex anatomy and/or physiology

Abstract: Introduction: Permanent junctional reciprocating tachycardia (PJRT) is a rare supraventricular tachycardia (SVT), typically involving a single decremental posteroseptal accessory pathway (AP). Methods: Four patients with long RP SVT underwent electrophysiology (EP) study and ablation. The cases were reviewed. Results: Case 1 recurred despite 3 prior ablations at the site of earliest retrograde atrial activation during orthodromic reciprocating tachycardia (ORT). Mapping during a repeat EP study demonstrated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…[3][4][5] Previous studies emphasized the importance of ventricular stimulation during tachycardias such as His refractory PVCs and VOD pacing to determine ventricular fusion, PPI-TCL and SA-VA measurements, as well as recording orthodromic His and right bundle activation sequence during entrainment. [1][2][3][4][5][6][7][8][9][10] In this series, we described 7 cases of cNV or cHV pathway-mediated arrhythmias and focused on several novel observations in response to ventricular pacing. Moreover, we studied the important roles of paradoxical atriohisian response in long RP tachycardia as well as use of adenosine in distinguishing cNV versus cHV pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Previous studies emphasized the importance of ventricular stimulation during tachycardias such as His refractory PVCs and VOD pacing to determine ventricular fusion, PPI-TCL and SA-VA measurements, as well as recording orthodromic His and right bundle activation sequence during entrainment. [1][2][3][4][5][6][7][8][9][10] In this series, we described 7 cases of cNV or cHV pathway-mediated arrhythmias and focused on several novel observations in response to ventricular pacing. Moreover, we studied the important roles of paradoxical atriohisian response in long RP tachycardia as well as use of adenosine in distinguishing cNV versus cHV pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Concealed nodo-ventricular (cNV) or concealed His-ventricular (cHV) pathways are rare accessory pathway (AP) variants that may be involved in the mechanism of reentrant supraventricular tachyarrhythmias (SVTs). 1–10 These arrhythmias represent important challenges for the clinician to separate from the more common arrhythmia mechanisms. Hence, the introduction of newer approaches to raise suspicion of the presence of these pathways as well as proof that these pathways are a critical part of the reentrant circuit is always important.…”
mentioning
confidence: 99%
“…Although PJRT can be found at any age, beginning in the fetal period, the majority of research and case reports in the children's age range are under the age of 1 year. 8 - 11 However, there have been studies conducted on adults. The mean age in our study was found to be greater than in other pediatric age group studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is a type of arrhythmia that occurs due to an uncommon reentrant mechanism and, in most cases, a decreasing posteroseptal accessory pathway with low conduction velocity does participate 45 . Characteristically, it is incessant, and electrocardiographic features are those of a tachycardia with regular, narrow QRS complexes, with a very long RP interval and a normal PR interval, but with an abnormal P wave axis, unlike in sinus rhythm.…”
Section: Reciprocal Junctional Tachycardiamentioning
confidence: 99%